Menelaah Empat Aliran Psikologi Pendidikan: Sintesis Konseptual dan Relevansinya dengan Pendidikan Islam - Yan Fathur Rahman; Heri Gunawan; Dede Rubai Misbahul Alam (CV. ITTC INDONESIA, 2026)
Educational psychology provides an essential foundation for understanding the learning process and developing effective instructional strategies. This article aims to analyze the four major schools of educational psychology behaviorism, cognitivism, constructivism, and humanism and examine their relevance to Islamic education. This study employs a library research method using a descriptive-analytical approach by reviewing books, scholarly articles, and other relevant literature on educational psychology and Islamic education. The findings indicate that each school offers distinct perspectives and contributions to the learning process. Behaviorism emphasizes observable behavior through stimulus, response, and reinforcement; cognitivism focuses on mental processes, conceptual understanding, and cognitive development; constructivism views learners as active agents who construct knowledge through experience and social interaction; while humanism emphasizes the holistic development of learners by nurturing their intellectual, emotional, social, and spiritual potential. These four schools are closely aligned with the principles of Islamic education, including the cultivation of moral character, reflective thinking (tafakkur), consultation (shūrā), and the development of the insan kamil (the complete human being). Therefore, educators are encouraged to integrate these educational psychology approaches contextually according to students' characteristics and instructional objectives in order to create meaningful, effective, humanistic, and character-oriented learning experiences.